The essence of digital business transformation - J. Boldareva; D. Lostanova (Вестник Северо-Кавказского федерального университета, 2022)
Within the framework of this article, the problems of the essence of the digital transformation of business as a significant trend of our time are considered. This trend is directly related to widespread digitalization, as well as to specific formats of business adaptation to this trend, which is the foundation of the digital transformation of the business sector. The purpose of this article is a comprehensive study of the essence of digital business transformation, using the example of the catering sector. A comprehensive analysis of the concept of digital business transformation is carried out, based on the range of opinions of specialists and specialized organizations. Special attention is paid to the definition and essence of the concept of digital transformation, the differences between this concept and digitalization are highlighted. It is noted that the result of the transformation should be the formation of a flexible organization capable of tracking adverse changes and new opportunities in the external and internal environment, and most importantly – having the ability to adapt to them in a timely manner.